Development of Nutraceutical Ice Creams Using Flour Yellow Worm Larvae (Tenebrio molitor), Chia (Salvia hispanica), and Quinoa (Chenopodium quinoa) - Hernández Toxqui, Ana Gabriela; Ramírez Ramírez, Jazmín; Pino Moreno, José Manuel; Talamantes Gómez, José Moisés; Angeles Campos, Sergio C.; Ramírez Orejel, Juan Carlos (Frontiers in Veterinary Science, 2021)
Functional food ice cream was developed by adding flours from larvae of the insect Tenebrio molitor mixed with a seed (Salvia hispanica) and a pseudocereal (Chenopodium quinoa) to strawberry-cranberry ice cream. The objective was to increase macro, micronutrients and antioxidants, thus rendering the product a food complement. Four ice cream formulas were manufactured: the control strawberry-cranberry ice cream and three experimental mixtures, one of them with an addition of Tenebrio larvae (HT) and the two others with a combination of Tenebrio larvae, chia (HTC) and quinoa (HTQ). The ice cream was submitted to proximate chemical analysis: mineral, fatty acid, vitamin and one antioxidant (cyanidin-3-glucoside) determination. The strawberry-cranberry ice cream was used as a control formula to evaluate if there were significant differences among nutrients, to whit a Dunnett test with a critical value of α= 0.05% was applied. The three formulas that were studied showed a significant increase in the analyzed macro and micronutrients compared to the control formula. We observed increases up to 62% in lipid content in the HTC formula, while an increase of 41% in the protein content of the HT formula was observed. We quantified an increase and enrichment of vitamins and minerals in the manufactured products, so that their nutritional value was significantly enhanced. Mention that anthocyanins make this group of flavonoids; stand out for their antioxidant and antimutagenic capabilities. In the determination of cyanidin-3-glucoside we found that the formula to which chia had been added showed an increase of 74% as compared to the control ice cream.